Atividade física e uso de drogas entre estudantes de ensino fundamental e médio - Romero, Luiz Rogério; Dalben, Ivete [UNESP] (My University, 2012)
The research examines the relationship between drug use and physical activity in school. We used an anonymous self-questionnaire among students in elementary and middle school in a Brazilian city. The mean age was 15.1 ± 1.5 years. There was no significant difference between energy expenditure and drug use, crack use except in life that related to significantly higher values of energy expenditure and habitual for the past thirty days, cocaine use was associated with higher energy expenditure habitual (p <0.05). We emphasize the need investigations addressing specific features of involvement in school and extracurricular activities, physical activity, drug use and their contributions to school health.

A pesquisa analisa a relação entre o uso de drogas e atividade física de escolares. Foi utilizado questionário anônimo de autopreenchimento entre estudantes de ensino fundamental e médio de um município brasileiro. A idade média foi de 15,1 ± 1,5 anos. Não houve diferença significativa entre gasto energético e uso de drogas, excetuando o uso de crack na vida que se relacionou a valores significativamente superiores de gasto energético habitual e em relação aos últimos trinta dias, o uso de cocaína associou-se ao maior gasto energético habitual (p<0,05). Ressalta-se a necessidade investigações específicas abordando características do envolvimento com atividades escolares e extracurriculares, prática de atividade física, uso de drogas e respectivas contribuições a saúde do escolar.
Physical activity and drug use among students of elementary and high school
Keywords: Motor activity; Students; Questionnaire; Street drugs; Atividade física; Estudantes; Questionário; Drogas ilícitas